TEACHING SUSTAINABILITY ONLINE TO UNIVERSITY STUDENTS WITH THE USE OF INTERACTIVE PRESENTATION TOOLS: A CASE STUDY - Iryna Lytovchenko; Nataliia Yamshynska; Neonila Kutsenok; Violeta Filatova (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2021)
The study was aimed to analyse the efficiency of teaching sustainability online at ESP classes. The participants of the study were 33 second-year technical university students who studied Sustainable Development issues with the use of interactive presentation platforms Thinglink and Padlet which employed different multimedia resources - text, pictures, sound, animation, video. The students' attitudes toward sustainability issues before and after the experimental learning was measured with the use of the sustainability consciousness questionnaire developed by Gericke, Boeve‐de Pauw, Berglund and Olsson (2018). The analysis of changes in different parameters of engineering students' sustainability consciousness showed the feasibility and appropriateness of teaching sustainability in an ESP course. The students' answers showed an increase in their knowingness of issues of Sustainable Development and their more responsible environmental behaviour, which implies the importance of disseminating knowledge and educating people for building a sustainable future. Based on the results of our study, we can conclude that ESP is a course which can organically integrate sustainability topics into its curriculum and use a wide range of resources and materials about Sustainable Development, since the majority of them are in English and thus can contribute not only to Learning for Sustainability but also to language acquisition. The use of online presentation tools and a wide range of multimedia resources on their platforms makes the learning more interactive and motivating for students and stimulates them to active inquiry into sustainability issues.